The unknown man of the Vietnam war: how Pham Van Dong changed the life of American prisoners of war - Cohen, Courtney, author; Gudmestad, Robert, advisor; Yalen, Deborah, advisor; Mansfield, Mike, committee member; Garvey, Sara, committee member (Colorado State University. Libraries, 2026)
During the Vietnam War, hundreds of American soldiers were taken as prisoners of war (POWs) by the North Vietnamese. Upon capture, these POWs were treated horribly, as the rights granted to them through the Geneva Conventions of 1949 were not being followed. The food quality, living and sanitary conditions, and medical care were all poor. Torture was prominent in these camps as well. After 1969, however, conditions immediately began to improve, and torture essentially stopped. These changes occurred in the POW camps after the death of North Vietnamese President Ho Chi Minh, but the correlation between his death and the change of treatment in POWs has been left unanswered in the historical literature. This thesis is going to provide an interpretation of how the death of Ho Chi Minh affected the treatment of POWs. I will be making this argument through two historical lenses: the social and the political. Through a social perspective, I will use the auto-biographies and stories of POWs who recounted their time in North Vietnam to understand the shift in treatment. I will be examining the change in food quality, living and hygiene conditions, medical treatment, and why torture stopped. On the other hand, I will be exploring the political makeup of North Vietnam, and how the political structure and prominent figures, most notably President Ho Chi Minh and Prime Minister Pham Van Dong, influenced the treatment of POWs.
Keywords: Ho Chi Minh; prisoner of war; Geneva Conventions; Vietnam War; Pham Van Dong